Hubungan Antara Kelelahan Kerja Dengan Persepsi Tingkat Pelayanan Pada Perawat Bagian Rawat Inap Di Rumah Sakit Umum PKU Muhammadiyah Delanggu - KUMALASARI, LITA EKA, Kusuma Estu W, SKM., M.Kes (2017)
Fatigue is a mechanism of body protection in order to avoid any further damage in order to recover the body after had a rest. Usually, the fatigue can be found by the complained of the workers in each work unit, including nurses. Work fatigue will impact one's psychological condition of nurses. This research had aim to know the correlation between of work fatigue with perception of the level of service in nurse of inpatient care facility at RSU PKU Muhammadiyah Delanggu. This research method research design analytic observational with cross sectional design. Subject of the study were 62 nurses using exhaustive sampling. Measurement of work fatigue using a KAUPKK questionnaire and perception of the level of service in nurse by using a questionnaire taken from previous research. Data analysis using test statistics Spearman Rank. Statistical test results for work fatigue with perception of the level of service in nurse of medical ward with the value of p = 0.000. The conclusion of this study stated there is a relation between work fatigue with perception of the level of service in nurse of inpatient care facility at RSU PKU Muhammadiyah Delanggu.